A guanine to adenine mutation -76bp from the transcriptional start site decreases constitutive CYP1A2 expression in a novel mouse strain - Taylor, Russell Haywood (University of Ottawa (Canada), 2007)
Variations in the expression of drug metabolizing enzymes of the Cytochrome P450 superfamily are a principal cause of atypical reactions to therapeutics. The molecular mechanisms by which the metabolizing enzymes of the drug are regulated, and the effects of genetic variation on this regulation, are not completely understood. Cytochrome P450 1A2 (CYP1A2) is one such enzyme. The APN mouse strain has low expression of the CYP1A2 enzyme, relative to the C3H/HeJ strain. It was hypothesized that this difference in expression of the CYP1A2 was occurring as a result of a single nucleotide polymorphism at the Cyp1a2 locus. This work has demonstrated that this variation in CYP1A2 expression occurs at the level of transcription and that a single nucleotide change 76 base pairs upstream of the transcriptional start site was critical for promoter function. The mechanism of constitutive CYP1A2 expression involves a previously unidentified cis-acting element in this region.
Keywords: Biology, Genetics.